2016
DOI: 10.1530/eje-16-0015
|View full text |Cite
|
Sign up to set email alerts
|

Seventy two-hour glucose monitoring profiles in mild gestational diabetes mellitus: differences from healthy pregnancies and influence of diet counseling

Abstract: Objective: To study glucose profiles of gestational diabetes (GDM) patients with 72 h of continuous glucose monitoring (CGM) either before (GDM1) or after (GDM2) dietary counseling, comparing them with nondiabetic (NDM) controls. Design and methods: We performed CGM on 22 GDM patients; 11 before and 11 after dietary counseling and compared them to 11 healthy controls. Several physiological and clinical characteristics of the glucose profiles were compared across the groups, including comparisons for pooled 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
5
11
0
Order By: Relevance
“…This was comparable to the figure of 81.4% with blood glucose values below 95 mg/dl among women with GDM reported by Carreiro et al 9 Postprandial blood glucose values and time to peak in our study were also comparable. This was comparable to the figure of 81.4% with blood glucose values below 95 mg/dl among women with GDM reported by Carreiro et al 9 Postprandial blood glucose values and time to peak in our study were also comparable.…”
Section: Main Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…This was comparable to the figure of 81.4% with blood glucose values below 95 mg/dl among women with GDM reported by Carreiro et al 9 Postprandial blood glucose values and time to peak in our study were also comparable. This was comparable to the figure of 81.4% with blood glucose values below 95 mg/dl among women with GDM reported by Carreiro et al 9 Postprandial blood glucose values and time to peak in our study were also comparable.…”
Section: Main Findingssupporting
confidence: 92%
“…All our women with GDM had fasting blood glucose levels far below 92 mg/dl as evidenced on the AGP recording. This was comparable to the figure of 81.4% with blood glucose values below 95 mg/dl among women with GDM reported by Carreiro et al 9 Postprandial blood glucose values and time to peak in our study were also comparable. 9 The present study shows significant differences in preprandial and postprandial blood glucose values between the three groups, with blood glucose values higher in GDM subjects at all points of time, compared with healthy pregnant subjects.…”
Section: Main Findingssupporting
confidence: 92%
“…These data show that a diet high in complex CHO and reduced fat still achieved glycemia below current treatment targets and lower postprandial free fat acids. Subsequently, Carreiro et al, 2016 [95] used CGM to more accurately assess the impact of dietary recommendations on women suffering from gestational diabetes and they concluded that dietary counseling was able to keep glucose levels close to those of healthy patients. In a prospective observational study with GDM patients two methods to evaluate glucose readings, CGM and self-monitor blood sugar glucose (SMBG), during Ramadan fasting were compared [96].…”
Section: Application Of Continuous Glucose Monitoring To Facilitate Cmentioning
confidence: 99%
“…Studies with CGM have helped to unmask important features such as glucose exposure and variability, in addition to glucose peaks related to meals [ 30 , 31 , 32 ]. They have also been extremely useful in strengthening our understanding of normal pregnancy glucose profiles, as well as to disclose differences from diabetic pregnancies [ 33 ]. The relationship between CGM data and pregnancy outcomes needs further clarification, in order to better understand which glucose features really impact on outcomes.…”
Section: Comprehensive Glucose Management: Beyond Glucose Time Poimentioning
confidence: 99%
“…This study suggests that targeting specific glucose time points may occasionally miss important glucose variations. It also suggests that, whenever glucose exposures are equal, variability and/or other factors other than glucose may be related to poor outcomes, such as fetal overgrowth [ 33 ].…”
Section: Comprehensive Glucose Management: Beyond Glucose Time Poimentioning
confidence: 99%